Euphoria Versus Sufferings: Revolutionary Rolpa in Post Conflict Context - Ghimire, Sachin (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
Armed conflict has left behind a legacy of social separation, physical loss of human lives and a population suffering from many kinds of physical and mental morbidities. In the post-conflict context, a lengthy political transition, coterie politics and the absence of a stable government are severely hindering the realisation of people's aspirations. Such hindrances have fostered a deep level of political frustration and promoted a culture of depoliticization. In Rolpa, lack of political commitment has meant people's health has become an overlooked agenda and has forced people to lose hope for change and survive with silent sufferings. Through the lens of a value-critical approach, this paper attempts to explore the relationship between politics of exclusion and its reflection on individual level pain and suffering in Rolpa.